2014
DOI: 10.1007/s11538-014-0024-x
|View full text |Cite
|
Sign up to set email alerts
|

Autocatalysis in Reaction Networks

Abstract: The persistence conjecture is a long-standing open problem in chemical reaction network theory. It concerns the behavior of solutions to coupled ODE systems that arise from applying mass-action kinetics to a network of chemical reactions. The idea is that if all reactions are reversible in a weak sense, then no species can go extinct. A notion that has been found useful in thinking about persistence is that of "critical siphon." We explore the combinatorics of critical siphons, with a view toward the persisten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…In their work on autocatalysis of reaction networks [15], Abhishek and Manoj showed that a consistent reaction network is self-replicable if and only if it is critical. Since weak-reversibility implies consistency and our definition of reversibility implies weak-reversibility, we obtain the following equivalence: let a chemical reaction network C be reversible.…”
Section: Summary Of Results and Connection With Existing Workmentioning
confidence: 99%
“…In their work on autocatalysis of reaction networks [15], Abhishek and Manoj showed that a consistent reaction network is self-replicable if and only if it is critical. Since weak-reversibility implies consistency and our definition of reversibility implies weak-reversibility, we obtain the following equivalence: let a chemical reaction network C be reversible.…”
Section: Summary Of Results and Connection With Existing Workmentioning
confidence: 99%
“…We say that a reaction network has the siphon/P-semiflow property if every siphon contains the support of a P-semiflow. △ Nonempty sets of species not containing the support of a P-semiflow are also known in the literature as critical [9]. So, a reaction network has the siphon/P-semiflow property if, and only if every siphon is noncritical.…”
Section: Siphons P-and T-semiflows Drainable Sets and Self-replicabmentioning
confidence: 99%
“…Since the seminal works of Horn, Jackson and Feinberg in the 70's ( [11,17,18], and references therein), chemical reaction network theory (CRNT) has provided a fruitful framework to study the dynamical systems describing how the concentrations of the involved chemical species evolve over time. Of great interest has been the long-term behavior of these systems, for example, whether they may exhibit oscillatory behavior [12], local asymptotic stability [2,3,12,16,26], or persistence [4,6,8,9,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations